Improving the legal policy system to develop the social work sector in Vietnam in the context of international integration - Doan, Khac Hung (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
Resolution No. 06-NQ/TW of the Fourth Plenum of the 12th Central Committee of the Communist Party of Vietnam (“Resolution 06”) [1] outlines strategies and policies for effectively implementing the process of international economic integration while maintaining political and social stability in the context of Vietnam's participation in newgeneration free trade agreements. The resolution highlights the importance of addressing social issues, including developing the social work sector in Vietnam. In accordance with the government's Resolution No. 22/NQ-CP on May 28, 2009[2], the Prime Minister of Vietnam issued Decision No. 32/2010/QD-TTg (“Decision 32”) [3] to approve the plan for developing social work from 2010 to 2020. However, 12 years have passed since then, and many objectives have yet to be achieved. The lack of legal tools is currently hindering the development of the social work sector, making it necessary to improve the legal policy system in Vietnam to promote the sector's development in the context of international integration.